Pengaruh Fisioterapi Dada, Batuk Efektif dan Nebulizer terhadap Peningkatan Saturasi Oksigen dalam Darah pada Pasien PPOK - Nurmayanti Nurmayanti; Agung Waluyo; Wati Jumaiyah; Rohman Azzam (Jurnal Keperawatan Silampari, 2019)
The purpose of this study was to determine the effect of chest physiotherapy, effective coughing, and nebulizer on increasing oxygen saturation in blood in COPD patients at Jakarta Cempaka Putih Islamic Hospital. The design of this research is Quasi Experiment using observation method with One Group Pre-Post Test design approach. Statistical results of paired T test (Wilcoxon test) for the value of p = 0.001 (p <0.05). Conclusion, there is an effect of giving chest physiotherapy, effective cough and nebulizer to increase oxygen saturation in blood before and after intervention in COPD patients. Keywords: Effective Cough Chest Physiotherapy, Nebulizer, COPD, Oxygen Saturation